Reference ranges of fetal superior vena cava blood flow velocities and pulsatility index in the second half of pregnancy: a longitudinal study - Maria Stefopoulou; Lotta Herling; Jonas Johnson; Peter Lindgren; Torvid Kiserud; Ganesh Acharya (BMC, 2021)
Abstract Background Fetal superior vena cava (SVC) is essentially the single vessel returning blood from the upper body to the heart. With approximately 80-85% of SVC blood flow representing cerebral venous return, its interrogation may provide clinically relevant information about fetal brain circulation. However, normal reference values for fetal SVC Doppler velocities and pulsatility index are lacking. Our aim was to establish longitudinal reference intervals for blood flow velocities and pulsatility index of the SVC during the second half of pregnancy. Methods This was a prospective study of low-risk singleton pregnancies. Serial Doppler examinations were performed approximately every 4 weeks to obtain fetal SVC blood velocity waveforms during 20-41 weeks. Peak systolic (S) velocity, diastolic (D) velocity, time-averaged maximum velocity (TAMxV), time-averaged intensity-weighted mean velocity (TAMeanV), and end-diastolic velocity during atrial contraction (A-velocity) were measured. Pulsatility index for vein (PIV) was calculated. Results SVC blood flow velocities were successfully recorded in the 134 fetuses yielding 510 sets of observations. The velocities increased significantly with advancing gestation: mean S-velocity increased from 24.0 to 39.8 cm/s, D-velocity from 13.0 to 19.0 cm/s, and A-velocity from 4.8 to 7.1 cm/s. Mean TAMxV increased from 12.7 to 23.1 cm/s, and TAMeanV from 6.9 to 11.2 cm/s. The PIV remained stable at 1.5 throughout the second half of pregnancy. Conclusions Longitudinal reference intervals of SVC blood flow velocities and PIV were established for the second half of pregnancy. The SVC velocities increased with advancing gestation, while the PIV remained stable from 20 weeks to term.